Exploring Student-Administration Relations in Educational Institutions: A Multifaceted Analysis - Chaudhary, Rajeshwer Prasad (Nepal Journal of Multidisciplinary Research, 2023)
Through an in-depth investigation, this article explores the intricate relationship between students and administration in educational institutions. In order to comprehend the mechanisms that shape a vital relationship, the study looks into a variety of aspects, including communication, resource allocation, leadership, conflict resolution, and student empowerment. To obtain the research objectives, the researcher distributed 60 Likert scale structured questionnaires directly to the students in the 10 different colleges for the data collection. The data were collected from March 10 to April 25 2023. The survey research design was used. The collected data was analyzed using the SPSS 20 and excel software to determine the results. The statistical tools correlation and regression were used to analyze the data. The findings provided insights into the effectiveness of communication channels, equity in resource distribution, leadership impact on student engagement, conflict resolution strategies, and student empowerment initiatives. Thus, this investigation enhances our comprehension of the intricate relationships between students and administration, assisting in developing more encouraging and inclusive learning environments.